A STUDY OF SUPPLY CHAIN MANAGEMENT IN INDONESIAN MODERN FOOD RETAILING CHAINS FOR FRESH VEGETABLE (CASE STUDY: FARM PRODUCER COMPANY, PT. SAUNG MIRWAN, BOGOR, INDONESIA) - Yanti Nuraeni Muflikh (Jurnal Agribisnis dan Ekonomi Pertanian, 2008)
Supply Chain Management (SCM) forces business practitioners to focus more on ultimate consumers’ needs. The purpose of this study was to examine the management issues against the six key principles of supply chain management (SCM). Electronic mails and phone interviews with management of PT Saung Mirwan were used to collect primary data about the dimensions of supply chains associated with the six key principles of SCM. This paper shows that the firm has tried to apply the six key principles of SCM although for several aspects the realization was still ineffective and inefficient. Perhaps main limitation of this was its narrow focus on one agribusiness company, thus precluding the generalization of findings to other sectors. Moreover, this study did not involve the company’s partners directly to result in the more accurate data. The findings reinforce the important of developing and maintaining closer relationship with chain’s partners in response to the change in business environments and serving better their end users.